Pengaruh Similarity, Expertise dan Likeability Terhadap Impulse Buying Tendency Melalui Parasocial Interaction pada Followers Instagram @Awkarin di Kota Padang - Ririn Safira Meidiani; Abror Abror; Yunita Engriani (Universitas Negeri Padang, 2019)
This study analyzes:(1) The effect of similarity towards parasocial interactionon followersinstagram @awkarin in the city of Padang, (2) The effect of expertisetowards parasocialinteractionon followers instagram @awkarin in the city of Padang, (3) The effect oflikeabilitytowards parasocial interactionon followers instagram @awkarin in the city of Padang,(4) The effect of parasocial interaction towards impulse buying tendency on followers instagram@awkarin in the city of Padang. This type of research is causative research. This research wasconducted in the city of Padang. The population in this study is the people of Padang who haveaccessed instagram. This study analyzed the data by using structural equation modelling (SEM)with smart PLS 3.0 as the software package. The results of this study indicate that: (1)Similarityhas a significant effect towards parasocial interaction on followers instagram @awkarinin the city of Padang, (2) Expertise has a significant effect towardsparasocial interaction onfollowers instagram @awkarin in the city of Padang, (3) Like ability has a significant effecttowards parasocial interaction on followers instagram @awkarin in the city of Padang (4)Parasocial Interaction has a significant effect towardsimpulse buying tendency on followersinstagram @awkarin in the city of Padang.Keywords: Impulse Buying Tendency, Parasocial Interaction,Similarity, Expertise, Likeability,Instagram,Causative Research